How we treat neurological toxicity from immune checkpoint inhibitors. (31st July 2019) - Spain, Lavinia; Tippu, Zayd; Larkin, James M; Carr, Aisling; Turajlic, Samra
Abstract : Neurological adverse events from immune checkpoint inhibition are increasingly recognised, especially with combination anti-cytotoxic T-lymphocyte antigen 4 (CTLA4) and anti-programmed death receptor 1 (anti-PD-1) therapies. Their presenting symptoms and signs are often subacute and highly variable, reflecting the numerous components of the nervous system. Given the risk of substantial morbidity and mortality, it is important to inform patients of symptoms that may be of concern, and to assess any suspected toxicity promptly. As with other immune-related adverse events, the cornerstone of management is administration of corticosteroids. Specialist neurology input is vital in this group of patients to guide appropriate investigations and tailor treatment strategies.